Foreign direct investment and local spillovers in the apparel sector in Sub-Saharan Africa - Cornelia Staritz (Austrian Foundation for Development Research (ÖFSE), 2013)
Foreign direct investment (FDI) in the apparel sector in several Sub-Saharan African (SSA) countries has experienced significant growth in the context of preferential market access. But expectations of FDI leading to spillovers to the local economy and the development of locally-embedded apparel export industries have not materialized. A shift from FDI attraction through fiscal incentives to more strategic industrial policies that target FDI spillovers, local value added and linkages is urgently needed for broader local development effects.
Keywords: 330; Auslandsinvestition; Spillover-Effekt; Bekleidungsindustrie; Afrika südlich der Sahara